PENGARUH KEPEMIMPINAN CAMAT TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR CAMAT ANGGANA KABUPATEN KUTAI KARTANEGARA - ., Suprasmanto (PREDIKSI, 2012)
This Research aims: 1) Knowing leadership model going into effect in Â environment of Office of Sub-Rege ncy Chief of Anggana of Regency of Kutai Kartanegara 2) Leadership Influence to discipline work Officer in Office of Sub-Regency Chief of Anggana of Regency of Kutai Kartanegara. Result from this research conclude that 1) Leadership going into effect in environment of Sub-Regency chief of Anggana predominated by style of leadership of transaksional and transformasional. Â Result of hypothesis test indicate do not there are relation significant leadership with the discipline work at Office of Sub-Regency Chief of Anggana of Regency of Kutai Kartanegara.